ANALISIS PENGARUH GAYA HIDUP HEDONIS,TEKANAN TEMAN SEBAYA,LITERASI KEUANGAN,EFIKASI DIRI DAN MEDIA SOSIAL TERHADAP PERILAKU KONSUMTIF MAHASISWA DI UNIVERSITAS PRIMA INDONESIA - Selvia, Cindy; Simanungkalit, Gloria Zefania; Dini, siti; Sakuntala, Dwita (Mount Hope Economic Global Journal, 2026)
This study aims to examine the influence of a hedonic lifestyle, peer pressure, financial literacy, self-efficacy, and social media on the consumer behavior of students at Universitas Prima Indonesia. The research approach used was quantitative with descriptive methods. The study population consisted of 300 students from various faculties. The sample was determined using simple random sampling, and based on the Slovin formula with a 5% margin of error, 171 respondents were obtained. The research data were primary data collected through questionnaires and analyzed using SPSS version 25. The analysis techniques used included validity testing, reliability testing, descriptive statistical analysis, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and hypothesis testing using t-tests, F-tests, and the coefficient of determination (R²). The results are expected to identify variables that significantly influence student consumer behavior, both partially and simultaneously. These findings are expected to contribute to the development of consumer behavior studies and serve as a reference for students in financial management and controlling consumer behavior.